Existence and Well-Posedness for Symmetric Vector Quasi-Equilibrium Problems - Kaihong Wang; Wenyan Zhang; Min Fang (Abstract and Applied Analysis)
An existence result for the solution set of symmetric vector quasi-equilibrium problems that allows for discontinuities is obtained. Moreover, sufficient conditions for the generalized Levitin-Polyak well-posedness of symmetric vector quasi-equilibrium problems are established.